Social Aspects in Technology Acceptance: Theory Integration and Development - Niehaves, Björn; Gorbacheva, Elena; Plattfaut, Ralf (45th Hawaii International Conference on System Sciences (HICSS-45), 2012)
The success of many new technologies and technology-based applications relies heavily on considering social factors. Contemporary models for technology acceptance either neglect social aspects or cover them in a superficial way. In our study we develop a better understanding of social aspects in technology adoption. We analyze and combine items related to social influence from the Unified Theory of Acceptance and Use of Technology and the Model of Adoption of Technology in Households and develop a new research model. While testing this model using quantitative data (n=501), one derived construct appears to be weak. Hence, we introduce new items, provide a second round of data collection (n=682), and develop an improved research model, which is validated by the new data. Here, all constructs work as intended. Our second model has a higher coefficient of determination than the first one. We show that Social Externalities is the most influential social factor towards technology acceptance and provide the corresponding items for future research.